Parallel Screening with 14C‐Labeled Carbon Dioxide: De‐risking the Staudinger‐Aza‐Wittig Reaction. Issue 30 (10th June 2022) - Babin, Victor; Sallustrau, Antoine; Molins, Maxime; Labiche, Alexandre; Goudet, Amélie; Taran, Frédéric; Audisio, Davide
Abstract: Carbon isotope labeling is a useful technology for tracking the fate of organic compounds in the environment and in living organisms. In this context, the development of robust and general methodologies amenable to the direct functionalization of CO2 remains a significant task. In this communication, a de‐risking approach was developed to evaluate the robustness of the Staudinger aza‐Wittig sequence for carbon isotope labeling. This technology is based on [ 14 C]CO2 screening that allowed to investigate the tolerance of the procedure with most representative heterocycles and functional groups found in FDA approved drugs. Abstract : A de‐risking approach was developed to evaluate the robustness of the Staudinger aza‐Wittig sequence. This technology is based on [ 14 C]CO2 screening that allowed to investigate the tolerance of the procedure with most representative heterocycles and functional groups found in FDA drugs.